The Usage of Electronic Academic Database Resources Among Lecturers and Postgraduate Students in Western Delta University, Oghara, Delta State, Nigeria - Saadatu Eireyi-Fidelis; Oghenetega Ivwighreghweta (International Journal of Librarianship (IJoL), 2022)
This study investigated the usage of electronic academic databases resources by lecturers and postgraduate students in Western Delta University, Oghara, Delta State, Nigeria. Four objectives with conforming research questions guided the study. The study adopted a descriptive research design. The population of the study consisted of 134 lecturers and postgraduate students in WDU. The instrument for data collection was a structured questionnaire with the title “Usage of Electronic Academic Database Resources Questionnaire (UEADRQ)”. Data was analyzed using frequency counts and percentages. The findings showed that there was a high level of awareness of the electronic academic database by the lecturers and postgraduate students. JSTOR, Elsevier, DOAJ, ProQuest, Science direct, and LexisNexis where been put to maximum usage. Meanwhile, NUC Virtual library, HINARI, Research4life, AGORA and EBSCO Host were used least frequently. The purposes of using the electronic academic datasets were for research, writing of seminar/conference paper, assignments/seminar presentations and getting up-to-date information with subject areas. Lack of search skill, slow internet bandwidth and incessant power outrage were some of the problems preventing against the effective usage of electronic academic database resources in WDU. Based on the findings of this study, it was concluded that electronic academic databases are vital information resources that need to be readily available in academic libraries for use by lecturers and students in the pursuit of their academic advancement. This study recommended that orientation, workshop and seminar should be organized by librarians and university authorities on how to acquire the needed search skills in order to be able to make adequate use of these electronic academic database resources in order to advance academic excellence.